The Perceived Meaning of Verbal and Non-Verbal Expressions in Chitato “Life is Never Flat” Advertisement - Clarista Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2019)
This thesis mainly deals with verbal and non-verbal expression to uncover hidden messages in the video commercial of Chitato themed ‘Life is Never Flat’, starred by Agnes Monica, taken from Youtube Channel. The writer focuses on the lyrics, the actress, as well as the colors involved in the scenes, and relates them to the theories of Chandler on verbal and non-verbal expression in order to find perceived meanings. In the analysis, the writer uses the theories to find out some hidden messages got by respondents after they watch the video commercial. In the analysis, the writer used descriptive qualitative method as her approach to describe meanings in the advertisement as her research. The respondents participated in the interview in order to find the hidden messages are ten people, consisting of old and young people. Based on the analysis, the writer has found out that the commercial of Chitato’s delivered denotation and connotation through its lyrics, the actress, and the colors. In conclusion, based on the result, the writer has found that Chitato’s advertisement invites audiences to feel great and enjoy their day by spending time with Chitato. Keywords: perceived meanings, advertisement, descriptive qualitative